The gender role on moderator effect of food safety label between perceived quality and risk on fresh vegetables - Adasme-Berríos, Cristian; Sánchez, Mercedes; Mora, Marcos; Schnettler, Berta; Lobos, Germán; Díaz, José (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
The role of food safety label in fresh vegetables has received little attention in developing economies and less attention from the perspective of gender. In this context, a conceptual model was developed to explain the effect of food safety label as a moderator variable of risk perception and quality perceived for fresh vegetables from the perspective of gender. A structural equation model was developed in central and south central Chile, using a convenience sample (n = 1114) of vegetables buyers. The main finding of the study was that for females, the food safety label moderated the effect of risk perception on perceived quality; while for males this effect was not significant. However, given that females are primarily responsible for purchasing food, food safety labels are a tool for consumers to recognize unsafe vegetables; at the same time, it can influence the purchase decision of those consumers worried by certain risks associated with fresh vegetables.